Facebook Spam Detection Extension Tool for Chromium Browser Architecture - Azman, Luqman Khir; Abdullah, Nurul Azma (Applied Information Technology And Computer Science, 2023)
Facebook has gained tremendous popularity worldwide, revolutionizing the way people consume news and eliminating the need for physical newspapers. However, this widespread usage has also exposed users to certain vulnerabilities, particularly the pervasive issue of spam. The prevalence of spam on Facebook not only disrupts user experience but also raises concerns about potential device damage. To address this problem, we propose the development of the "Facebook Spam Detection Extension Tool" - a browser extension designed specifically for Google Chrome. This tool aims to identify and filter spam within the Facebook domain, providing users with a safer and more enjoyable browsing experience. The extension will employ various techniques for spam detection, including content analysis of messages and identification of behavioral patterns commonly associated with spam. By implementing this tool, we can effectively reduce unwanted and annoying communication while safeguarding users against malicious activities.